Development of antiangiogenic agents for ovarian cancer. Issue 1 (January 2008) - Collinson, Fiona J; Hall, Geoff D; Perren, Timothy J; Jayson, Gordon C
Epithelial ovarian cancer (EOC) remains a major source of cancer morbidity and mortality, despite advances in surgical and chemotherapeutic management. The molecular pathways that control angiogenesis have been demonstrated to be key to the pathogenesis of EOC, and have been shown to have prognostic significance. Increased understanding of the pathways and molecules involved in angiogenesis has allowed the identification of a number of targets for antiangiogenic therapies and the development of a variety of antiangiogenic drugs. There is now significant preclinical evidence, and a growing body of clinical data, demonstrating promising results with antiangiogenic drugs in the treatment of EOC. Single-agent VEGF inhibitor response rates in pretreated patients of between 15 and 20% have been reported, with much higher response rates when used in combination with chemotherapeutic agents. These benefits, however, must be balanced with the toxicities associated with these drugs, particularly the more serious ones, such as gastrointestinal perforation. The results of ongoing and future randomized clinical trials will confirm if, and how, antiangiogenic therapies should be integrated into the routine management of EOC. However, critical issues, such as the relative importance of combination remission induction regimens and maintenance therapy, remain poorly defined.